(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
The collectives that face politically the dominant order produce discourses through which they discuss, at various levels, those stereotypes imposed by the dominant discourse. In cases of lesbian collectives, those emerging representations redefine derogatory clichés or stereotyped poses. This paper proposes a critical reading of the http://adoratrixsdelavlvapeluda.blogspot.com; http://escritosheréticos.blogspot.com and http://malascomolasa.blogspot.com/ blogs, in order to study their discursive modes and political poses linked to the ethos that those building identities assume, tensioned between the need of images to be identified in connection with a group and the recognition of the oppressive nature of the concept of identity. If this is defined from an illusory consensus, little sensitive to difference and multiplicity, Sylvia Molloy’s concept of pose redefines identity as something transient, arbitrary or eccentric, open to the possibility of being other/ s. This analysis focuses on subjectivity and language and relationship with other/ s, to try an approach to the forms assumed by the ethos in those discourses, as a cultural sign that tries to escape the identity mandates of the dominant culture.